Velikost in oblika krošnje pri bukvi (Fagus sylvatica L.) in smreki (Picea abies (L.) Karst) - Polenšek, Maja (Gozdarski vestnik, 2006)
The shape and size of crowns within a stand vary considerably from tree to tree, hence determining the shape and size of a crown can often be problematic. The most accurate data can be obtained by sectioning the crown. It is however often difficult to get sufficient data in a stand, so we examined whether the crown shapes of spruce and beech trees could be calculated by an analytic function. We studied the shape and size of the crownin a stand of growing trees, specifically Common Beech and Norway Spruce,according to their diameter class. For this purpose we photographed whole trees in the field with a digital camera. The comparison showed that theanalytic function is accurate enough to determine the values of crown surface, but the volumes proved to be more discrepant. Formulas for cone and paraboloid describe crowns inaccurately, in most cases underestimating them. The relationship between crown width and DBH (tree diameter at breast height) can be described well by an allometric function.
Keywords: smreka; Picea abies; bukev; Fagus sylvatica L.; krošnja; dendrometrija